Thermodynamic and kinetic analysis of the chemical reaction of methanol dehydration to formaldehyde - V. F. Tretyakov; A. M. Ilolov; R. M. Talyshinsky; N. A. Frantsuzova; A. S. Popov (Тонкие химические технологии, 2009)
Theoretical analysis of the possibility of conjugating the reaction of formaldehyde formation via dehydrogenation of methanol with other initiating reactions is conducted; and advantages of using hydrogen peroxide vs. organic inductors are discussed. When hydrogen peroxide is used, the reaction reaches stationary condition almost immediately. It is demonstrated that the induction and the targeted reaction proceed with high selectivity towards formaldehyde.